Quale Self? - Pappagallo, Elena; Dell’Erba, Alice; Monducci, Elena (Il sogno della farfalla, 2016)
In this paper, the authors suggest a reflection on the issue of pre-psychotic symptoms, which are considered to be nuclear and pathognomonic of schizophrenia. They start by outlining the historical aspects, proposing valid psychopathogical descriptions dating back to the early 20th century, which were lost in favour of the Anglo-American operational diagnosis (explicit diagnostic criteria). Then, they move on to describe the recent remarkable recovery of these concepts by the Danish school headed by Josef Parnas, whilst highlighting their intrinsic limits due to their having little application to therapeutic and research domains as well as to the lack of valuable thought on the etiology and the pathogenesis of schizophrenia. Finally, the authors describe how this historical gap may be filled with the interpretation of pre-psychotic experiences in the light of the Human Birth Theory proposed by Massimo Fagioli, which offers a rigorous and valid instrument for research and treatment.